Hello,
I've tried to get a solution of this problem and I failed very successfully
Could it be that the proportion reads:
AD : DC = 2 : 1 (?)
If so, the solution is:
1. AD = u + v
2. AD = 2*DC ==> DC = (1/2)*AD
3. BC = -u + AD + DC
BC = -u + u+v + (1/2)*(u+v) = v + (1/2)*u + (1/2)*v = (1/2)*(u + 3v)
Hi,
now it's me who is really confused - because:
AC = AD + DC. Therefore:
AC/DC = 2 ==> AC = 2*DC ==> AD + DC = 2*DC ==> AD = DC
From my previous post you know that
BC = -u + AD + DC
BC = -u + u+v + u+v = u + 2v
This answer differs slightly( ) from the given answer.
(Could it be that ... ahemm?)